Stress-strain state and dynamics of the allochthonous part of the Precarpathian trough in connection with oil and gas content (according to tectonophysical data) - Gintov, O.B.; Bubnyak, I. N.; Bubnyak, A. N.; Vikhot, Yu. M.; Mychak, S. V.; Nakapelyukh, M. V. (Geofizicheskiy Zhurnal, 2013)
Results of tectonophysical studies of the Scyba, Boryslav-Pokut and Sambor nappes of the Ukrainian Carpathians have been presented. Their deflected mode, regional and local fields of strain have been considered and age relations have been specified. It has been shown that the Boryslav-Pokut nappe, in contrast to Scyba nappe after total Carpathian compression suffered sufficiently strong all-round extension that resulted on one hand in saturation of its interior part with hydrocarbons but on the other hand in escape of gas component.